(untitled) (Contemporary Journal of Social Science Review, 2025)
War has a profound impact on history, shaping societies and lives, and with the advent of nuclear weapons after World War II, warfare took a sophisticated and lethal turn. Conventional war between major powers has become outdated, focusing on displaying capabilities for deterrence. In the twenty first century, warfare has transformed from conventional battlefield confrontation into a multidimensional struggle involving cyber-attacks, disinformation campaigns, economic coercion, diplomatic isolation, proxy warfare, and psychological operations. This modern form of conflict is widely known as hybrid warfare. Pakistan, due to its strategic geography, ideological identity, economic vulnerabilities, and regional rivalries, has become a major target of such warfare. India-Pakistan relations, shaped by historical hostility and strategic competition, provide a significant case for understanding how hybrid warfare operates in South Asia. This research critically examines Indian hybrid warfare against Pakistan and explores its strategic implications. It analyses how hybrid warfare combines conventional and unconventional means to weaken the target state without direct full scale war. The study investigates India‟s strategic objectives, including political destabilization, economic weakening, diplomatic isolation, exploitation of ethnic and sectarian divisions, and the sabotage of Pakistan‟s strategic partnerships, particularly with China. The study also evaluates the Doval Doctrine, covert operations, proxy warfare, cyber-attacks, media manipulation, and fifth generation warfare as major instruments of hybrid conflict. Special attention is given to the 2025 India-Pakistan confrontation, particularly the large scale aerial dogfight and Pakistan‟s retaliatory military response. This event demonstrated how conventional warfare and hybrid warfare are now deeply interconnected. Electronic warfare, cyber preparedness, media narratives, diplomatic messaging, and missile technology became as important as physical combat itself. The study employs a qualitative research methodology based on Strategic Theory rooted in the work of Carl Von Clausewitz and Grand Strategy Theory developed by B. H. Liddell Hart. This theoretical framework provides a comprehensive lens to examine the changing nature of warfare, particularly the shift from conventional conflict to hybrid warfare. Strategic Theory explains how states use ways and means to achieve political objectives, while Grand Strategy Theory expands this understanding by including military, diplomatic, economic, informational, and psychological dimensions of conflict. The findings reveal that hybrid warfare has emerged as one of the most serious national security challenges for Pakistan, requiring a comprehensive response based on cyber security, strategic communication, economic resilience, institutional coordination, and national unity.